EXPLORING THE INFLUENCE OF SOCIAL MEDIA MARKETING, EWOM, AND BRAND IMAGE IN INCREASING PURCHASE INTENTION FOR NPURE PRODUCTS ON TIKTOK (A CASE STUDY ON GEN Z IN YOGYAKARTA) - Sufi Dewi Utami; Elisa Jayanti Lestari (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2025)
This study examines the influence of social media marketing, electronic word-of-mouth (eWOM), and brand image on purchase intention toward NPure skincare products on TikTok among Generation Z consumers in Yogyakarta. TikTok has become one of the most impactful digital platforms for shaping consumer perceptions, particularly in the beauty industry where short-video content, peer reviews, and influencer endorsements strongly affect purchasing behavior. Grounded in the Theory of Planned Behavior (TPB), this research adopts a quantitative approach with a causal explanatory design. Data were collected from 160 respondents using a purposive sampling technique targeting active TikTok users aged 13–28 who are familiar with NPure products. Measurement instruments were adapted from validated indicators and assessed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate the relationships among variables. The results show that social media marketing, eWOM, and brand image each have a significant and positive effect on purchase intention. These findings highlight the effectiveness of TikTok as a marketing channel, demonstrating that engaging content, credible online reviews, and strong brand perceptions play essential roles in influencing consumer decisions. The study provides empirical insights into digital marketing practices in the skincare industry and reinforces the importance of integrating interactive social media strategies to enhance consumer purchasing interest.